2016
DOI: 10.1007/s00265-016-2226-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated reproduction does not affect telomere dynamics and oxidative stress

Abstract: Oxidative stress and telomere dynamics are considered to be powerful biomarkers quantifying a potential trade-off between current reproduction and self-maintenance. Recent studies confirmed the negative impact of elevated reproduction on telomeres, but the evidence for the cost of reproduction in terms of oxidative stress remains equivocal. In order to induce reproductive costs, we experimentally manipulated reproductive effort by increasing brood size in captive zebra finches (Taeniopygia guttata) and additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
(84 reference statements)
0
17
0
Order By: Relevance
“…As demonstrated in experimental studies [10,11], telomere shortening possibly reflects cumulative DNA damage caused by high reproductive effort. Elevated reproduction may cause telomere shortening owing to faster cellular turnover and overproduction of telomere-damaging free radicals by increasing metabolic rate ( [19,20], but see [21,22]), but also divert resources from telomere maintenance, i.e. telomerase activity or antioxidant protection [1,23].…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in experimental studies [10,11], telomere shortening possibly reflects cumulative DNA damage caused by high reproductive effort. Elevated reproduction may cause telomere shortening owing to faster cellular turnover and overproduction of telomere-damaging free radicals by increasing metabolic rate ( [19,20], but see [21,22]), but also divert resources from telomere maintenance, i.e. telomerase activity or antioxidant protection [1,23].…”
Section: Resultsmentioning
confidence: 99%
“…Especially in terms of female reproduction, a meta-analysis from different homeothermic vertebrates by Blount et al [ 8 ] has shown that in intraspecific comparisons between breeders and non-breeders, breeders had lower levels of oxidative damage in certain tissues. This effect could be attributed to upregulation of antioxidant defense mechanisms, such as glutathione or superoxide dismutase activity, which shows a tissue-dependent upregulation in several species during reproduction [ 36 39 ]. This oxidative shielding hypothesis, even if not consistent across different studies (reviewed in: [ 8 ]), suggests a reproduction-induced protection of mothers and offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, few studies quantify the "effort" of the animals, for example in terms of their energy expenditure, and so are unable to show a link between effort and measures of senescence such as reduced survivability (though see: Daan et al, 1996). Moreover, there is only one study (and it is on captive animals-zebra finches), that includes measures of oxidative stress, DNA damage and survival (Sudyka et al, 2016). Hence, studies published so far investigating activity correlates of wild animal senescence have failed to combine all the following crucial elements: quantified physical activity, physiological and DNA damage, and measures of functional or demographic senescence.…”
Section: Physical Activity Aging and "Effort"mentioning
confidence: 99%